2008
DOI: 10.1172/jci36168
|View full text |Cite
|
Sign up to set email alerts
|

AIP1 functions as an endogenous inhibitor of VEGFR2-mediated signaling and inflammatory angiogenesis in mice

Abstract: ASK1-interacting protein-1 (AIP1), a recently identified member of the Ras GTPase-activating protein family, is highly expressed in vascular ECs and regulates EC apoptosis in vitro. However, its function in vivo has not been established. To study this, we generated AIP1-deficient mice (KO mice). Although these mice showed no obvious defects in vascular development, they exhibited dramatically enhanced angiogenesis in 2 models of inflammatory angiogenesis. In one of these models, the enhanced angiogenesis obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
130
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(136 citation statements)
references
References 51 publications
6
130
0
Order By: Relevance
“…3 However, DAB2IP knockout (KO) mice are viable and develop normally, arguing against a major role of this protein in embryogenesis and differentiation. 4,5 Regarding its mechanism of action, DAB2IP has an enzymatic activity whose core lies in the Ras-GAP domain. In addition, DAB2IP acts as an adaptor, or scaffold, in protein complexes relevant for signal transduction, and it can function as a competitor, or scavenger, by binding signaling proteins and preventing their interaction with upstream activators, or downstream effectors (Table 1).…”
Section: Dab2ip: a Complex Gene Encoding A Negative Modulator Of Multmentioning
confidence: 99%
See 4 more Smart Citations
“…3 However, DAB2IP knockout (KO) mice are viable and develop normally, arguing against a major role of this protein in embryogenesis and differentiation. 4,5 Regarding its mechanism of action, DAB2IP has an enzymatic activity whose core lies in the Ras-GAP domain. In addition, DAB2IP acts as an adaptor, or scaffold, in protein complexes relevant for signal transduction, and it can function as a competitor, or scavenger, by binding signaling proteins and preventing their interaction with upstream activators, or downstream effectors (Table 1).…”
Section: Dab2ip: a Complex Gene Encoding A Negative Modulator Of Multmentioning
confidence: 99%
“…10,11 Interestingly, animal models showed that DAB2IP functions as endogenous inhibitor of adaptive angiogenesis in part by binding directly to VEGFR-2 and limiting PI3K activation ( Figure 4b). 4 GSK3β-β-catenin signaling. GSK3β is a ser/thr kinase that phosphorylates numerous substrates, often triggering their degradation.…”
Section: Dab2ip: a Complex Gene Encoding A Negative Modulator Of Multmentioning
confidence: 99%
See 3 more Smart Citations